2021
DOI: 10.1177/15330338211041472
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lipid Profiles in Human Non-Small Cell Lung Cancer

Abstract: Aims: This review aims to identify lipid biomarkers of non-small cell lung cancer (NSCLC) in human tissue samples and discuss the roles of lipids in tissue molecular identification, the discovery of potential biomarkers, and surgical margin assessment. Methods: A review of the literature focused on lipid-related research using mass spectrometry (MS) techniques in human NSCLC tissues from January 1, 2015, to November 20, 2020, was conducted. The quality of included studies was assessed using the QUADAS-2 tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Glycerophospholipid metabolism is highly related to the development and progression of cancer ( Yang et al, 2022 ). A review of 12 articles showed that the phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol, cardiolipin, phosphatidylserine, phosphatidylglycerol, ceramide, lysophosphatidylethanolamine, lysophosphatidylcholine, and lysophosphatidylglycerol levels were significantly different between NSCLC and normal tissues ( Jianyong et al, 2021 ), which was consistent with what we observed in the serum of NSCLC patients. After treatment with EGFR-TKIs or PD-1/PD-L1 inhibitors, the levels of various glycerol phospholipids tended to decrease to levels similar to those in the HC group, indicating that these two treatments may block the dysregulation of lipid metabolism in tumor cells to a certain extent to exert antitumor therapeutic effects.…”
Section: Discussionsupporting
confidence: 87%
“…Glycerophospholipid metabolism is highly related to the development and progression of cancer ( Yang et al, 2022 ). A review of 12 articles showed that the phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol, cardiolipin, phosphatidylserine, phosphatidylglycerol, ceramide, lysophosphatidylethanolamine, lysophosphatidylcholine, and lysophosphatidylglycerol levels were significantly different between NSCLC and normal tissues ( Jianyong et al, 2021 ), which was consistent with what we observed in the serum of NSCLC patients. After treatment with EGFR-TKIs or PD-1/PD-L1 inhibitors, the levels of various glycerol phospholipids tended to decrease to levels similar to those in the HC group, indicating that these two treatments may block the dysregulation of lipid metabolism in tumor cells to a certain extent to exert antitumor therapeutic effects.…”
Section: Discussionsupporting
confidence: 87%
“…NFY (Nuclear factor Y) is a transcriptional factor that may identify CCAAT boxes in the promoter and is also involved in the lipogenesis process and other biological functions. NFY was also found to be upregulated in the LC samples with a poor clinical outcome [ 129 ].…”
Section: Major Metabolic Pathway Changes Involved In Lung Canermentioning
confidence: 99%
“…Studies have focused on the importance of fatty acids and phospholipids in NSCLC [ 129 ]. Serum lipidome screening in NSCLC patients has identified phosphatidylcholine and lysophosphatidylcholines as major diagnostic biomarkers for the LC [ 130 ].…”
Section: Major Metabolic Pathway Changes Involved In Lung Canermentioning
confidence: 99%
“…With the recent advancements in mass spectrometry technology, lipidomics has been utilized as a new field for exploring cancer biomarkers [ 12 ]. Cancer cells exhibit a common phenotype of uncontrolled proliferation, and their lipid metabolism is altered to generate energy and biomass components efficiently [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%